MENCOBA REALIS DALAM KARYA LUKIS - Viomela Martin; Eerfahmi .; Muzni Ramanto (Universitas Negeri Padang, 2012)
Abstract When a person feels the love for something, someone can be him self and not confined within the space they created their own fantasies. On the way to achieve not only the sweet taste of love and happiness that is felt. Occasionally feeling sad, disappointed, hurt, and tired of being colorful in the process of achievinga sense of love.The endof this present work that a imstoprovide an understanding that, ashuman beings should beable to live and deal with all the problems oflife with the realistic. Inthe works ofauthors display characters or objects that represent the the meandin accordance with the concept ofauthor's works. in his final painting, the cultivation techniquesof realist endstoenhance the dimensions of the object creation form. The effectof allthe problems that have been passedin this lifecanassistin achieving the process of maturation and maturityin attitude. Kata Kunci : Mencoba Realis, Karya Lukis